A study on the Driving factors of Foreign Institutional Investment in Indian Stock Market (BSE) - Arpita Tripathi , Dr. Arun Gautam, Prof. Renu Pareek (Journal of Informatics Education and Research, 2024)
India's stock market is essential to the country's economic progress. The market for stocks is an assembly point where investors, including residents and non-residents, may invest or withdraw money in the hope of seeing a capital increase. The stock market is an essential actor in the financial industry because it gives users and suppliers of financial resources a place to invest in company stocks. Examine the FII’s link with the stock market of India’s average monthly return. Monthly statistics were gathered for six years, from the beginning of 2016 to the end of 2021, to assess the impact of FII on the comeback of stock market of India. The relationship between the return of stocks and these variables was investigated using economic analysis. Every factor, such as the Sensex (BSE), and FII (both dependent and independent) are included in the analysis to check the stationary before being employed in the econometric analysis. The ADF test was used to assess the validity of the unit root test. The preceding study demonstrates that there is a causal link between the FII and the Sensex has been studied using correlation and the Granger causality test.